The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1994
DOI: 10.1002/cyto.990150307
|View full text |Cite
|
Sign up to set email alerts
|

Further flow cytometric studies of the effects of triethylenemelamine on somatic and testicular tissues of the rat

Abstract: Exposure to the mutagen triethylenemelamine on rat bone marrow, blood, and testis was studied using flow cytometry of DAPI-stained nuclei. Increased coefficients of variation (CVs) of the GI peaks were observed in bone marrow and blood after both 1 d and 5 d exposures. After 5 d exposure and 7 d recovery both tissues had recovered, in some cases to significantly lower CVs. Increased CVs of the 1C peak of testis were observed only after 5 d exposure to the high dose with no subsequently observed recovery. Bone … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

1994
1994
2009
2009

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 28 publications
2
14
0
Order By: Relevance
“…This distress may be indicative of toxicological antagonism at an end point other than chromosomal damage. Two recent studies have observed a similar phenomenon in whole animal studies and reached similar conclusions (18,22). This hypothesis is further supported by the observation that when all three herbicides are combined at the lower concentrations, the CVs are higher than the CVs of cells exposed to the same trio of chemicals at a higher concentration (see Tables 1 and 2).…”
Section: Discussionsupporting
confidence: 75%
“…This distress may be indicative of toxicological antagonism at an end point other than chromosomal damage. Two recent studies have observed a similar phenomenon in whole animal studies and reached similar conclusions (18,22). This hypothesis is further supported by the observation that when all three herbicides are combined at the lower concentrations, the CVs are higher than the CVs of cells exposed to the same trio of chemicals at a higher concentration (see Tables 1 and 2).…”
Section: Discussionsupporting
confidence: 75%
“…Nuclei of disrupted kidney, liver and spleen cells were stained with propiduim iodide and analysed with a Coulter Profile II flow cytometer (Coulter Electronics Inc., Krefeld, Germany) equipped with a 488‐nm Argon laser. The cytometer was adjusted to fit the G1/G0 peak of chicken red blood cells on channel 250 (Bickham et al ., 1994). DNA content was estimated as the ratio of X divided by the mean channel number of the G1/G0 peak for the animal tested, multiplied by 2.54 (pg DNA) over channel 250 for the chicken red‐blood cell standard (Fisher et al ., 1994).…”
Section: Methodsmentioning
confidence: 99%
“…FCM was used to estimate DNA content variation within red blood cells (RBC) of both European pond turtles (Emys orbicularis) and Caspian turtles (Mauremys caspica). This method has been shown to be an effective biomarker of chromosomal damage, caused by a variety of contaminants including PAHs, radionuclides, and some pesticides, in many wildlife studies McBee and Bickham, 1988;Dallas and Evans, 1990;George et al, 1991;Lamb et al, 1991Lamb et al, , 1995Bickham et al, 1992Bickham et al, , 1994Custer et al, 1994;Lingenfelser et al, 1997aLingenfelser et al, , 1997bLowcock et al, 1997;Theodorakis et al, 2001;Matson et al, in press). Of more importance to this study is the fact that flow cytometry data tend to correlate well with petroleum products and PAHs in particular (Bickham et al, 1998a;Custer et al, 2000).…”
Section: Introductionmentioning
confidence: 93%